(untitled) (Columbus, OH., 2009)
Use SRA Real Math's true-to-life applications, standards-based curriculum, and extensive teacher resources to help your students develop essential math skills through engaging and exciting lessons. Differentiated instruction helps you reach every student in your classroom. Make AYP and meet California state standards with a proven, quality education for all students, including students in need of intervention, English-language learners, and high-achieving students ready for enrichment.
Keywords: Mathematics,Toán học; Study and teaching (Elementary),Nghiên cứu và giảng dạy (Tiểu học)